A Study of the Relationship Between Students’ Global Perspective and Willingness to Communicate in English at an English Medium Instruction University in China - Xiao, Yuehai; Qiu, Xiang (Frontiers in Psychology, 2022)
Few of the previous studies had investigated the relationship between global perspective (GP) and willingness to communicate (WTC) in English, hence the correlation between them needs to be validated by more studies (Fang, Chen & Elyas, 2020). Furthermore, there are hardly any pertaining studies conducted at EMI universities. As such, the current study aimed to fill these gaps in the context of an EMI university in south China, by investigating whether GP correlates with L2 WTC and what factors impact the two variables. Data were collected from students via an online questionnaire (n=315) and follow-up interviews (n=11). The questionnaire findings confirm that there is a moderate positive correlation between GP and L2 WTC. The interview data unravel that there are a few factors influencing students’ L2 WTC, including needs and motivations driving L2 WTC, concerns constraining L2 WTC, and intercultural cognition facilitating L2 WTC. These findings suggest that： A) students could be more determined to practice their English if they realize the significance of the role of English in their life; B) teachers could foster student’s WTC in English by creating a nonthreatening English-speaking environment and encouraging students to communicate in English in and outside the classroom; and C). teachers could educate students about GP and L2 WTC, which might help to expand students’ horizon and stimulate their interests in foreign cultures and global affairs, so as to facilitate the sustainable growth of their English learning.